POTRET KONFLIK SOSIAL DI KABUPATEN KUANTAN SINGINGI TAHUN 2013 - Marta, Auradian (Universitas Riau, 2014)
This research is motivated by the social conflict in the Kuantan Singingi Regency highimpact on the surrounding environment. The aim of this study determines the source of conflictand effort of handling conflicts in the Kuantan Singingi Regency. The method used in this studyis to use a qualitative approach and using the techniques of data collection through interviews,documentation and observation studies. The results showed that the source of conflict in KuantanSingingi Regency sourced from the economic interests of each actor and conflict resolution isdone by consensus and law enforcement.Keywords: social conflict, sources of conflict